Multicombination Approach Suppresses Listeria monocytogenes‐Induced Septicemia‐Associated Acute Hepatic Failure: The Role of iRhom2 Signaling. Issue 17 (26th June 2018) - Xu, Min‐Xuan; Ge, Chen‐Xu; Qin, Yu‐Ting; Gu, Ting‐Ting; Lou, De‐Shuai; Li, Qiang; Hu, Lin‐Feng; Tan, Jun
Abstract: The mortality rate of acute liver failure significantly increases due to fatal septicemia. Inactive rhomboid protein 2 (iRhom2) is an essential regulator of shedding TNF‐α by trafficking with TNF‐α converting enzyme (TACE). Fisetin, a flavonoid present in various fruits and plants, possesses anti‐oxidative stress and anti‐inflammatory activities. Here, multi‐combination nanoparticles Fe@Au conjugated with fisetin, iRhom2 small interfering RNA (siRNA), and TNF‐α inhibitor (FN) are prepared to examine their effects on fatal septicemia‐associated hepatic failure induced by Listeria monocytogenes (LM) in mice and to reveal the underlying mechanisms. After LM infection, upregulation of glutamic‐oxalacetic transaminease, glutamic‐pyruvic transaminase, alkaline phosphatase, TNF‐α, malondialdehyde, H2 O2, and O2 ‐ is observedcompared to FN‐treated mice. The iRhom2/TACE/TNF‐α signals are enhanced in vivo and in vitro, resulting in oxidative stress, which is especially associated with the activation of kupffer cells and other macrophages. Decrease in Nrf2 activation and increase of inflammation‐associated regulators are also noted in vivo and in vitro. Furthermore, overexpression of TNF‐α derived from macrophages aggravates hepatic failure. Inversely, the processes above are restored by FN nanoparticles through the regulation of the iRhom2/TACE/TNF‐α axis and Nrf2 activation. These findings suggest that FN may be a potential approach to protect against bacterial septicemia‐related diseases by targeting iRhom2. Abstract : A multicombination strategy containing fisetin, small interfering RNA (siRNA) of inactive rhomboid protein 2 (iRhom2), and TNF‐α inhibitor nanoparticles for Listeria monocytogenes ‐induced acute hepatic failure targeting is constructed in this study. The nanoparticles are released by a lysosome, resulting in reduction of iRhom2/TNF‐α converting enzyme/NF‐κB activation, suppression of pro‐oxidants and proinflammatory cytokines and chemokines, further promoting the remission of septicemia‐induced liver failure.